1998
DOI: 10.1093/carcin/19.5.711
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted roles of nitric oxide in cancer

Abstract: The roles of nitric oxide (NO) in numerous disease states have generated considerable discussion over the past several years. NO has been labeled as the causative agent in different pathophysiological mechanisms, yet appears to protect against various chemical species such as those generated under oxidative stress. Similarly, NO appears to exert a dichotomy of effects within the multistage model of cancer. Chronic inflammation can lead to the production of chemical intermediates, among them NO, which in turn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
381
1
22

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(411 citation statements)
references
References 131 publications
3
381
1
22
Order By: Relevance
“…However, the potential usefulness of nitroglycerin to make tumoral tissue more permeable to gene therapy vectors should be compounded by the possible anti-apoptotic effects of this substance for neoplastic cells 46 and the possibility that its vasoactive properties might favor metastasis. 47 In addition, the dose of nitroglycerin which has been administered in the present study is about 10 to 20 times greater (on a body weight basis) than the dose of intravenous nitroglycerin employed in patients with heart disorders. 48 This might be an additional limitation to the use of nitric oxide donors to enhance vascular permeability in solid tumors.…”
Section: Figure 4 Immunohistochemical Localization Of ␣-Sma Positive mentioning
confidence: 69%
“…However, the potential usefulness of nitroglycerin to make tumoral tissue more permeable to gene therapy vectors should be compounded by the possible anti-apoptotic effects of this substance for neoplastic cells 46 and the possibility that its vasoactive properties might favor metastasis. 47 In addition, the dose of nitroglycerin which has been administered in the present study is about 10 to 20 times greater (on a body weight basis) than the dose of intravenous nitroglycerin employed in patients with heart disorders. 48 This might be an additional limitation to the use of nitric oxide donors to enhance vascular permeability in solid tumors.…”
Section: Figure 4 Immunohistochemical Localization Of ␣-Sma Positive mentioning
confidence: 69%
“…Tumor angiogenesis is stimulated by the release of several factors, such as endothelial growth factor, integrins, and immature dendritic cells, among others, to promote a rich oxygen supply for tumor growth 29, 30, 31. Other studies have reported that the release of nitric oxide by tumor cells causes vasodilation and increases the temperature in affected mammary glands 32, 33, 34. We believe that a combination of all these factors is responsible for the increase in temperature in neoplastic mammary glands in our study, as the controlled temperature in the room eliminated any influence from the ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that NO stimulates angiogenesis and mediates the effect of a number of angiogenic molecules (Ziche et al, 1994(Ziche et al, , 1997Parenti et al, 2001). In human tumours, NO plays an important role in tumour growth and progression (Wink et al, 1998), as also evidenced by the increased expression of nitric oxide synthase (NOS) found in a variety of tumours (Thomsen et al, 1994;Cobbs et al, 1995;Gallo et al, 1998;Klotz et al, 1998;Feng et al, 2002). Nitric oxide has been shown to be important for maintaining the vasodilator tone of tumours by regulating tumour blood flow (Fukumura et al, 1997), and is an active mediator of tumour angiogenesis (Gallo et al, 1998;Jadeski and Lala, 1999;Jadeski et al, 2000), intimately linked with cancer cell growth and metastasis.…”
mentioning
confidence: 84%